Humanitarian Engineering : Innovative Approaches and Partnerships in Crisis Response - Tayler, Yolanda (World Bank, Washington, DC, 2016)
The overall purpose was to identify how reconstruction of infrastructure and provision ofessential services could be more effective,especially in countries, such as Lebanon andJordan, facing a massive refugee crisis driven by the war in Syria. The attention of the international community is increasingly focusedon maximizing effectiveness in crisis response. That is underscored in the communiqué of therecent G7 summit in Japan, and in the recent UN World Humanitarian Summit in Istanbul, which highlighted the need for the humanitarian and development communities to collaborate inaddressing the special needs of growing numbers of people facing long-term crisis conditions. TheCyprus workshop was thus very timely,especially in identifying priority steps tooptimize the critical role of procurement, onwhich the effectiveness of crisis response ultimately depends. The notion of “Humanitarian Engineering” and the International Humanitarian Engineering Partnership (HEP) were key themes at the workshop. Humanitarian Engineering” hasbeen defined in terms of enhancing human and community welfare, including in situations of chronic distress of large numbers of people (e.g.,emergencies and refugee crises) and encompassing research, design, manufacturing,construction and service delivery. HEP engages key stakeholders to develop innovative approaches and tools for moreeffective crisis response, in particular in the procurement dimension. The critical need for resources being developedby HEP was highlighted by a May 2016 surveyconducted across regions. Practical information about effective crisisresponse procurement that HEP can disseminate was illustrated at the workshop. Traditionally, development organizations haveoperated outside the emergency context.However, with the rise in long-lasting crises, itis critical to coordinate with local and regional stakeholders such as Non-governmental organization (NGOs), humanitarian agencies, and private sector, including small and medium enterprises (SMEs). The World Bank’s participation in HEP builds on its commitment to addressing the regionalcrisis including the MENA Financing Initiative to support refugees, host communities, and recovery and reconstruction. Partnering with stakeholders such as International Federation of Consulting Engineers (FIDIC) in the HEP initiative provides a strategic multiplier for the Bank’s efforts in crisis response. The dialogue at the workshop suggests key takeaways for the way forward.